(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Red clover Trifolium pratense is one of the most popular legumes feed crops in North America and Europe. It is being sown in field and forage shifts of crops as such and mixed with cereals. Among the cultivated clover types (white, rose, crimson and red) the red one is the most widespread in Latvia. The field tests of lignosilicon (LSi), biologically active compound developed and synthesized in the Latvian state institute of Wood Chemistry has shown its favorable action when used in biological farming for oats and rye growth with red clover undersow. Years 2004-2006 tests in field conditions have proved LSi prolonged influence on red clover growth and development: green mass, dry matter content in it and protein content in crop significantly increase beginning with the first year of LSi application. Chemical analysis of roots and aboveground part of plants has shown increase in boron content in buds on the background o f240 kg/ha of LSi. At the same time, increase in silicon, iron, manganese and copper content has been observed in roots. After one year cultivation of clover “Divaja” brand on the background of LSi, an enrichment of soil with organic substances and nitrogen in comparison with control was observed.